Synthesis of Ca-hydroxyapatite Bioceramic from Egg Shell and its Characterization - Ahmed, Samina; Ahsan, Mainul (Bangladesh Journal of Scientific and Industrial Research, 2009)
Ca-hydroxyapatite (HA) was synthesised from egg shell under different conditions and characterised by using AAS, FT-IR, XRD, SEM and EDS techniques. The results of these analyses combined together indicate that sintered HA sample1 resembles the feature of pure and single apatite phase having hexagonal structure. A Ca/P molar ratio of 1.69 was achieved in this case. On the other hand HA obtained from calcined egg shell is a combination of both amorphous and crystalline phase and revealed a sub-stoichiometric Ca-deficient apatite form with a Ca/P ratio of 1.50. Keywords: Ca-hydroxyapatite, Biomaterials, Hexagonal, stoichiometric apatite, Ca-deficient apatite Â doi: 10.3329/bjsir.v43i4.2240 Bangladesh J. Sci. Ind. Res. 43(4), 501-512, 2008